Construction calculations manual - Levy, Sidney M. (Butterworth-Heinemann, 2012)
"Written by one of the premier professionals in the field, Construction Calculations Manual provides end users with the calculations necessary for ensuring the on-time project delivery, within-budget projects. The proposed book will provide an owner, planning a construction project, with detailed calculations regarding site work, piping and pipe fitting, cost estimation, and overall project management. The only book of its kind on the market today, this guide gives you all essential calculations used on the construction site. Day-to-day construction work calculations are presented in plain easy to read language. Time Saving calculations include: Complete Stair calculations for Risers, Treads, Stringer Length and Incline Angle Set Riser Height and solve for Stairwell Opening Built-in Right-Angle Functions for Square-ups, Slopes Area, Volume and Perimeter solutions with Length, Width and Height Keys Drywall, Siding and Paneling Key calculates Roof Function finds Area, Bundles, Squares and 4x8 Sheathing for Flat or Pitched Roofs Compound Miter - Store Crown Angle and Enter Wall Corner Angle to calculate the Blade Tilt and Angle for Miters cuts Board Feet Lumber estimating All calculations are categorized according to equipment type--and sample calculations, applications and examples are provided. With this book in hand, owners, construction managers, construction engineers, architects, and contractor will find manual a valuable guide to some of the most common and difficult calculations in all aspects of construction"-- Provided by publisher.
Includes index.
"Written by one of the premier professionals in the field, Construction Calculations Manual provides end users with the calculations necessary for ensuring the on-time project delivery, within-budget projects. The proposed book will provide an owner, planning a construction project, with detailed calculations regarding site work, piping and pipe fitting, cost estimation, and overall project management. The only book of its kind on the market today, this guide gives you all essential calculations used on the construction site. Day-to-day construction work calculations are presented in plain easy to read language. Time Saving calculations include: Complete Stair calculations for Risers, Treads, Stringer Length and Incline Angle Set Riser Height and solve for Stairwell Opening Built-in Right-Angle Functions for Square-ups, Slopes Area, Volume and Perimeter solutions with Length, Width and Height Keys Drywall, Siding and Paneling Key calculates Roof Function finds Area, Bundles, Squares and 4x8 Sheathing for Flat or Pitched Roofs Compound Miter - Store Crown Angle and Enter Wall Corner Angle to calculate the Blade Tilt and Angle for Miters cuts Board Feet Lumber estimating All calculations are categorized according to equipment type--and sample calculations, applications and examples are provided. With this book in hand, owners, construction managers, construction engineers, architects, and contractor will find manual a valuable guide to some of the most common and difficult calculations in all aspects of construction"-- Provided by publisher.
Keywords: Engineering mathematics.; elektronické knihy; electronic books